Kulturní centrum Kopřivnice - Benada, Marek (Vysoké učení technické v Brně. Fakulta architektury)
Cílem práce je nalezení přístupu k řešení transformace kulturních staveb ze 70. - 80. let 20.století, které postupně zastarávají jak technicky, tak morálně. Takovým příkladem může být konglomerát kulturního domu, kina a technického muzea, který se nachází v centrální zóně města Kopřivnice, jež po radikální asanaci v druhé polovině 20.století nedošla definitvní ucelené a funkční podoby.

The aim is to find the approach to the transformation of cultural constructions of 70 - 80 years of the 20th century, which gradually become obsolete, both technically and morally. An example may be a conglomerate cultural center, cinema and Technology Museum, located in the central zone of Koprivnica, which after radical renewal in the second half of the 20th century did not final, complete and functional form.
Cultural Center in Koprivnice
Keywords: Kulturní centrum v Kopřivnici; Culture center in Koprivnice